Tingkat Pemanfaatan Smartphone sebagai Media Informasi Pertanian oleh Petani Padi Desa Margomulyo Kecamatan Tayu Kabupaten Pati - Silva, Mariska Adinia; Gayatri, Siwi; Mariyono, Joko (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Fulfilling the need for agricultural information was the main focus of information and communication technology applications in agriculture. Smartphones were not only used to find agricultural information but also served as an extension media. This study aimed to identify the level of smartphone utilization as a media of agricultural information by rice farmers in Margomulyo Village and to formulate strategies for extension methods and media based on their perceptions. The research was conducted from January to February 2025 in Margomulyo Village using a survey method. Sampling was done purposively with 73 respondents for objective 1, including 8 farmer group leaders and 1 extension worker as key informants for objective 2. Data were collected through interviews, observation, and documentation. The analytical methods used were descriptive analysis and swot analysis. The results showed that smartphone utilization as a media of agricultural information was high, based on perceived usefulness (technological effectiveness, technological advantages, and the relevance of technology to achieve goals) and perceived ease of use (ease of learning, ease of use, and infrastructure availability). The extension methods and media for Margomulyo Village rice farmers were in quadrant I, suggesting an aggressive (S-O) strategy. S-O strategies that could be used included strengthening digital extension based on farmer groups, optimizing smartphones as extension media and information access, collaborating with extension workers and online farmer communities, and integrating technology in face-to-face extension.